2016
DOI: 10.1177/0284185115618547
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipoma with minimal fat: differentiation of morphological and enhancement features from renal cell carcinoma at CT imaging

Abstract: CT images with non-round shape without capsule and prolonged enhancements may be used to differentiate AML with minimal fat from RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…It was concluded that, in CT imaging, "non-round shape" in the absence of capsule and prolonged enhancement were factors that could distinguish minimal-fat AML from RCC [8]. Prolonged enhancement was also found to be an important radiological feature in distinguishing the two pathologies by Kim et al [9].…”
Section: Discussionmentioning
confidence: 96%
“…It was concluded that, in CT imaging, "non-round shape" in the absence of capsule and prolonged enhancement were factors that could distinguish minimal-fat AML from RCC [8]. Prolonged enhancement was also found to be an important radiological feature in distinguishing the two pathologies by Kim et al [9].…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][4] Could this patient have TSC, or could the angiomyolipoma be unusual renal metastases presenting radiologically as angiomyolipoma? [5] Could her freckles be mistaken for angiofibromas, which would support the diagnosis of tuberous sclerosis? These are important considerations in this case that may offer some treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that unenhanced CT images have an advantage when used to differentiate between two types of masses compared to phase CT images, most approaches incorporate both unenhanced and contrast‐enhanced (CE) CT images to classify renal masses . Lee‐Felker et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sung et al. evaluated several morphological features, including the degree of roundness and the presence of capsules, and enhancement patterns to differentiate between fp‐AML and RCC via chi‐square tests of unenhanced and early excretory phase CT . Ishigami et al.…”
Section: Introductionmentioning
confidence: 99%